(untitled) (Móin-Móin - Revista de Estudos sobre Teatro de Formas Animadas, 2020)
Questions of censorship and self-censorship are confronted through Julia Varley’s experience of animating a skull mask on stilts, Mr. Peanut, and a puppet, Sheherazade. Mr. Peanut travels to many Latin American countries, and the article remembers episodes from Ayacucho, Perú, and Santiago de Chile, and the meetings with soldiers and police.